A two-step numerical method for efficient analysis of structural response to blast load - Li, J.; Hao, Hong (Multi-Science Publishing Co. Ltd., 2011)
Even with modern computer power, detailed numerical modeling and simulation of structure response to blast loads are still extremely expensive and sometimes prohibitive because it is very time consuming and requires huge computer memory. Often compromise has to be made between simulation efficiency and simulation accuracy. A lot of research efforts have been spent on improving the computational efficiency. Most of these researches concentrate on simplifying the structures, such as simplifying a structure to an equivalent SDOF system, use smeared reinforcement steel and concrete model, use substructure approach to only model part of the structure in detail. Although these approaches under certain conditions yield reliable predictions, each of them has its associated limitations. Recently a two-step method was developed to improve the computation and modeling efficiency of structure response to blast loads. Instead of simplifying the structure, the proposed method calculates the structural responses in two steps. The first step calculates the structural responses in the loading phase and the second calculates the free vibration responses with the velocity profile of the structure at the end of the loading phase as initial conditions. Using a reinforced concrete beam as the example, it was found that the proposed method yields reliable predictions of the overall beam deflection and stress in longitudinal reinforcement bars with less than 10% computational time as compared to a detailed FE model simulation. However, the predicted stress in hoop reinforcements near the beam supports is not as good. In this paper, the method is improved by also including displacement response at the end of the forced-vibration phase as the initial conditions in the free vibration analysis. The same reinforced concrete beam is used. The results show that including the displacement initial conditions in the two-step method leads to an improved prediction of the beam responses. Parametric calculations are performed in this.